Metal–Organic Framework (MOF) Nanorods, Nanotubes, and Nanowires. Issue 20 (16th April 2018) - Arbulu, Roberto C.; Jiang, Ying‐Bing; Peterson, Eric J.; Qin, Yang
Abstract: New mechanisms for the controlled growth of one‐dimensional (1D) metal–organic framework (MOF) nano‐ and superstructures under size‐confinement and surface‐directing effects have been discovered. Through applying interfacial synthesis templated by track‐etched polycarbonate (PCTE) membranes, congruent polycrystalline zeolitic imidazolate framework‐8 (ZIF‐8) solid nanorods and hollow nanotubes were found to form within 100 nm membrane pores, while single crystalline ZIF‐8 nanowires grew inside 30 nm pores, all of which possess large aspect ratios up to 60 and show preferential crystal orientation with the {100} planes aligned parallel to the long axis of the pore. Our findings provide a generalizable method for controlling size, morphology, and lattice orientation of MOF nanomaterials. Abstract : Templated interfacial synthesis was applied to metal–organic framework (MOF) growth under both size‐confinement and surface‐directing effects. This led to congruent polycrystalline MOF nanorods and nanotubes, and single crystalline nanowires with large aspect ratios up to 60 and controlled crystal lattice orientation.